Arbitragem envolvendo a administração pública - Moura, Allan Vinicius de (2024)
This dissertation aims to resolve controversial issues in arbitration, which the Public Administration is part of. The specific objectives are to verify if the principle of unavailability of the public interest prevents the use of arbitration; to study the theories explaining the concept of available property rights; examine whether the appointment of arbitrators and the choice of arbitration chambers by the Public Administration should be the subject to the bidding or the process of unlawful bidding; examine whether the execution of arbitral sort that order of the Treasury to pay a certain amount must be submitted to the regime of precatory; check what kind of arbitration should be adopted by the Public Administration, institutional or ad hoc; investigate the appropriateness of reports on contractual and succumbing legal fees in the arbitration process; investigate whether arbitration can be used to settle disputes arising from the hiring of common goods or services by means of the negotiated procedure; examine whether the arbitrators should apply the binding judicial precedents provided for in the Code of Civil Procedure; verify which party must bear the costs and expenses for the initiation of arbitration proceedings; to investigate the possibility of submitting tax disputes to arbitration. The results show that the principle of unavailability of the public interest is consistent with the concept of available property rights, not preventing the Public Administration to use arbitration jurisdiction to resolve its conflicts. It is concluded that the choice of arbitrators and arbitration chambers by the Public Administration is not subject to bidding, nor to the procedure of unenforceability of bidding. It is demonstrated that compliance with arbitral awards that condemn the Treasury to pay a certain amount must be submitted to the regime of precatory or small value requisitions, depending on the value of the conviction, there can be no distinction between creditors of the Public Treasury supported by judicial decisions and creditors supported by arbitral awards. It is concluded that the sentence in arbitration fees is only valid if there is provision in the arbitration agreement, the arbitration term or the rules of the arbitration chamber chosen by the parties, while the compensation of contractual fees depends on the party’s request in its opening arguments. It appears that arbitration can be used to resolve conflicts arising from contracts bid through the trading mode. It is concluded that the arbitrator is not subject to the mechanical application of binding judicial precedents, and can overcome them, provided they are reasoned. It is concluded, in the end, there is no obstacle to the use of arbitration to resolve conflicts involving tax credit. The research methods used were literature review and jurisprudential research